The Fall of Fertility in Tasmania, Australia, in the late 19th and early 20th centuries - Helen Moyle (Historical Life Course Studies)
The paper examines the fall of marital fertility in Tasmania, the second settled Australian colony, in the late 19th and early 20th centuries. The paper investigates when marital fertility fell, whether the fall was mainly due to stopping or spacing behaviours, and why it fell at this time. The database used for the research was created by reconstituting the birth histories of couples marrying in Tasmania in 1860, 1870, 1880 and 1890, using digitised 19th century Tasmanian vital registration data plus many other sources. Despite Tasmania’s location on the other side of the world, the fertility decline had remarkable similarities with the historical fertility decline in continental Western Europe, England and other English-speaking countries. Fertility started to decline in the late 1880s and the fertility decline became well established during the 1890s. The fall in fertility in late 19th century Tasmania was primarily due to the practice of stopping behaviour in the 1880 and 1890 cohorts, although birth spacing was also used as a strategy by the 1890 cohort. The findings provide support for some of the prominent theories of fertility transition.